2019
DOI: 10.1017/s2045796019000192
|View full text |Cite
|
Sign up to set email alerts
|

The culture, mental health and psychosocial wellbeing of Rohingya refugees: a systematic review

Abstract: AimsDespite the magnitude and protracted nature of the Rohingya refugee situation, there is limited information on the culture, mental health and psychosocial wellbeing of this group. This paper, drawing on a report commissioned by the United Nations High Commissioner for Refugees (UNHCR), aims to provide a comprehensive synthesis of the literature on mental health and psychosocial wellbeing of Rohingya refugees, including an examination of associated cultural factors. The ultimate objective is to assist human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
138
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(140 citation statements)
references
References 14 publications
2
138
0
Order By: Relevance
“…Parallel but separate procedures were applied in developing and refining both the IAT and CBT interventions. The systematic process of cultural adaptation of both therapies was guided by the framework of Bernal and Saez-Sanriago [33] and based on an extensive review of cultural idioms of distress and local terminologies for mental health symptoms [34,35]. Parallel draft manuals and associated materials were translated into the relevant dialects with the assistance of bilingual mental health professionals.…”
Section: Development Adaptation and Piloting Of Interventions And Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Parallel but separate procedures were applied in developing and refining both the IAT and CBT interventions. The systematic process of cultural adaptation of both therapies was guided by the framework of Bernal and Saez-Sanriago [33] and based on an extensive review of cultural idioms of distress and local terminologies for mental health symptoms [34,35]. Parallel draft manuals and associated materials were translated into the relevant dialects with the assistance of bilingual mental health professionals.…”
Section: Development Adaptation and Piloting Of Interventions And Mmentioning
confidence: 99%
“…Strengths of the study include the systematic recruitment strategy in that participants were drawn from a representative sample of refugees from 3 community-based epidemiological studies, yielding a pool of participants that reflected the demographic profile of each; for example, our sample replicated the general pattern in the community by generating a larger sample of men amongst the Rohingya [38]. There was extensive work done to adapt and pilot the materials and procedures prior to conducting the RCT [34,35], including a systematic process of translation and adaptation of the manuals to ensure their cultural, contextual, and linguistic appropriateness. The entire intervention was conducted by lay counsellors from the respective communities, consistent with the principles of task shifting which enhances the capacity to scale up the interventions in real-life service settings.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The approach was both systematic and based on extensive less formal interactions during the process of engagement with each refugee group as well as with NGOs and UNHCR officers in both Malaysia and Bangladesh. The process of cultural adaptation was guided by the framework of Bernal and Saez-Santiago (2006), supplemented by information generated by a targeted desk review of cultural idioms of distress and local terminologies conducted in relation to each refugee group in each setting (see a comprehensive review of the Rohingya refugees (Tay et al, 2019b)). The first step was the translation of all materials including the manual into the appropriate dialects with the assistance of bilingual mental health professionals.…”
Section: Early Modifications Of the Iat Manual Amongst West Papuan Rementioning
confidence: 99%
“…A recent systematic review of 8,176 Syrian refugees resettled in 10 countries reported a prevalence of 43% for PTSD, 40% for depression, and 26% for anxiety [8]. As the literature has focused on either specific cultural groups or specific host nations or has combined internally displaced populations with refugees and asylum seekers, there is a lack of estimates on the prevalence of mental illness in more representative refugee and asylum-seeker populations [9][10][11][12]. There is also a lack of research investigating the full breadth of mental illness, as the literature has mainly focused on PTSD and depression, hence the need for a comprehensive, worldwide, systematic review to investigate mental illness in the current refugee populations.…”
Section: Introductionmentioning
confidence: 99%